Features of successful interventions to improve adherence to inhaled corticosteroids in children with asthma: A narrative systematic review. Issue 4 (21st February 2022) - Pearce, Christina J.; Chan, Amy H. Y.; Jackson, Tracy; Fleming, Louise; Foot, Holly; Bush, Andy; Horne, Rob
Abstract: Introduction: Nonadherence to inhaled corticosteroids (ICSs) in children with asthma leads to significant morbidity and mortality. Few adherence interventions have been effective and little is known about what contributes to intervention effectiveness. This systematic review summarizes the efficacy and the characteristics of effective interventions. Methods: Six databases were systematically searched on October 3, 2020 for randomized control trials measuring adherence to ICS in children with asthma. A narrative synthesis was conducted focusing on intervention efficacy and study reliability. Intervention content was coded based on the National Institute for Health and Care Excellence guidelines for medicines adherence (the Perceptions and Practicalities Approach, PAPA) and behavior change techniques (BCTs), to determine the effective aspects of the intervention. Results: Of 240 studies identified, 25 were eligible for inclusion. Thirteen of the 25 studies were categorized as being highly reliable. Nine of the 13 interventions were effective at increasing adherence and 6 of those met the criteria for a PAPA intervention. Techniques targeting perceptions and practicalities in successful interventions included rewards, reminders, feedback and monitoring of adherence, pharmacological support, instruction on how to take their ICS/adhere, and information about triggers for symptoms and nonadherence. Conclusion: Adherence interventions in children with asthma have mixed effectiveness. Effective intervention studies were more frequently of higher quality, were tailored to individuals' perceptual and practical adherence barriers, and used multiple BCTs. However, due to the small number of included studies and varying study design quality, conclusions drawn here are preliminary. Future research is needed to test a PAPA‐based intervention with a rigorous study design.